SYMPTOMATIC HYPERCALCEMIA IN WILLIAMS SYNDROME - Giridharan, Sharanya; Hui, Saw Shi (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Williams syndrome is a multisystem contiguous gene deletion syndrome that presents with distinctive facial features, congenital heart disease, neurodevelopmental and behavioral deficits. Endocrine abnormalities such as diabetes and hypothyroidism are described in adults while hypercalcemia is mostly reported in infants and young children during first 2 years of life. Hypercalcemia in Williams syndrome is usually mild and asymptomatic resolving by the age of two years. It may be associated with hypercalciuria and to a lesser extent nephrocalcinosis, occurring in less than 5% of WS patients. Traditional treatment of hypercalcemia in children with William Syndrome consists of intravenous hydration, dietary restriction of calcium and vitamin D and in unresponsive cases, intravenous biphosphonate may be considered as second line treatment. RESULTS We report 2 children with Williams syndrome who presented with symptomatic hypercalcemia associated with nephrocalcinosis. Both these patients required hospital admission around the age of 2 years old and responded to intravenous hydration. We intend to highlight that symptomatic hypercalcemia in children with Williams syndrome is not uncommon and that their elevated serum calcium levels can respond to increased hydration via enteral and parenteral route in parallel with dietary restrictions. CONCLUSION In conclusion, close monitoring of serum calcium levels as well as parental education on symptoms of hyper-calcemia and dietary advice is crucial in management of children with hypercalcemia in Williams syndrome.